Social contention, authoritarian resilience, and political change. Issue 6 (19th September 2017) - Fumagalli, Matteo
ABSTRACT: This article takes stock of recent advances in the field of comparative authoritarianism. The four books reviewed shed light on the effects of social activism, claim-making and social protests on authoritarian resilience. Taken as a whole, they intervene in the scholarly debates that examine the rise of collective, often contentious action under authoritarian rule. In so doing they account both for how states tolerate or even encourage collective action and the extent to which, in turn, protests by distinct social groups re-shape the political system. As authoritarian institutions, democratic-looking or otherwise, have received considerable attention of late, this article calls for greater attention to the economic and ideational dimensions of authoritarianism and, more generally, a broader research agenda.